Pemanfaatan AI dalam pembelajaran Pendidikan Agama Islam untuk mendukung SDGS - Ramadon, Gilang; Subagiya, Bahrum; Hidayat, Muhammad Faishal (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This study discusses the use of Artificial Intelligence (AI) in Islamic Religious Education learning to improve the quality and effectiveness of learning. The focus of the study includes opportunities, challenges, and strategies for optimizing the use of AI, especially in supporting adaptive, interesting, and relevant learning to the needs of students in the digital era. This study discusses students’ understanding of the use of AI in Islamic Religious Education learning, identifies the obstacles faced, and formulates strategies for effective use of AI so that the teaching and learning process becomes more optimal and relevant. This study uses a descriptive qualitative approach to understand the phenomenon in depth. Data were collected through observation and interviews, then analyzed to find patterns and meanings. The results are presented in narrative form to describe the real conditions of the research object. This study aims to describe students’ perceptions of the use of AI in Islamic Religious Education learning. Data were obtained through questionnaires and interviews. The results show how students view the use of AI in supporting a more effective and relevant learning process with the times. Abstrak Penelitian ini membahas pemanfaatan Artificial Intelligence (AI) dalam pembelajaran Pendidikan Agama Islam untuk meningkatkan kualitas dan efektivitas pembelajaran. Fokus penelitian mencakup peluang, tantangan, dan strategi optimalisasi pemanfaatan AI, khususnya dalam mendukung pembelajaran yang adaptif, menarik, serta relevan dengan kebutuhan mahasiswa di era digital. Penelitian ini membahas pemahaman mahasiswa terhadap penggunaan AI dalam pembelajaran Pendidikan Agama Islam, mengidentifikasi kendala yang dihadapi, serta merumuskan strategi pemanfaatan AI secara efektif agar proses belajar mengajar menjadi lebih optimal dan relevan. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk memahami fenomena secara mendalam. Data dikumpulkan melalui observasi dan wawancara, kemudian dianalisis untuk menemukan pola dan makna. Hasilnya disajikan dalam bentuk narasi untuk menggambarkan kondisi nyata objek penelitian. Penelitian ini bertujuan menggambarkan persepsi mahasiswa terhadap pemanfaatan AI dalam pembelajaran Pendidikan Agama Islam. Data diperoleh melalui kuesioner dan wawancara. Hasilnya menunjukkan bagaimana pandangan mahasiswa terhadap penggunaan AI dalam mendukung proses belajar yang lebih efektif dan relevan dengan perkembangan zaman.